IDENTIFICATION OF ENVIRONMENTAL HEALTH AND SAFETY IN FACTORY OF HOSPITAL BEDS AT. X BEKASI - Dwi Septian Wijaya; Wilda Maulida (Poltekkes Kemenkes Semarang, 2019)
In this globalization era, especially in the face of international trade competition then the principle of the application of health and safety are the main requirements that will greatly affect the investment value, quality, and quantity of products, the company's sustainability and competitiveness of a country. The purpose survey is to identify health and safety hazards which include chemical, physical, biological, ergonomic, and psychological hospital bed factory in PT. X Bekasi. The method used to survey and interview in the work unit welding, painting, assembling, and factory environments. Based on the survey results of the use of personal protective equipment (PPE) is pretty good and secure, while at 4 locations are all well qualified for occupational safety, health, and environment.